Smart Data Analysis with SmartPLS: Training for Students at the University of West Sulawesi - Basir, Badirun; Dollah, Abd. Latif (Unram Journal of Community Service, 2025)
Students' ability to perform quantitative data analysis, particularly using Partial Least Squares Structural Equation Modeling (PLS-SEM) based on SmartPLS 3.2.9, is still low and has an impact on the quality of student research. This community service activity aims to improve understanding of the basic concepts of PLS-SEM, train technical skills in operating SmartPLS 3.2.9, and strengthen students' abilities in processing and interpreting research data. The training lasted for two days, from September 13 to 14, 2025, and was attended by 79 students from the Management and Accounting Study Programs. The training method was participatory, involving material delivery, practical demonstrations, and case study-based exercises. The evaluation results showed a significant increase in participants' mastery, with the average pre-test score of 42% increasing to 86% on the post-test. This training proved effective in improving students' competence in research data analysis, while also strengthening the research culture at the University of West Sulawesi.